2023
DOI: 10.1038/s41562-022-01506-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the evidence on learning during the COVID-19 pandemic

Abstract: March 2021protocol via Twitter in order to crowd-source additional relevant studies not identified through the search. All titles and abstracts identified in our search were double-screened using the Rayyan online application. Fourth, to ensure that our analysis is comprehensive in terms of recent and relevant research, on February 14, 2022, and on August 8, 2022, we conducted two comprehensive forward and backward citation searches of all eligible studies identified in the above steps. As noted above, in orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
144
3
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(161 citation statements)
references
References 61 publications
8
144
3
6
Order By: Relevance
“…Not only are several new countries considered in the analysis (e.g., Slovenia, Egypt), but US and UK studies do not dominate the collected empirical evidence. For instance, while in Betthäuser et al (2023) about 71.1% of the effect sizes are derived from these studies, in our paper the corresponding figure is approximately 32.2%. 4 This makes our results of more general relevance.…”
Section: Introductioncontrasting
confidence: 42%
See 3 more Smart Citations
“…Not only are several new countries considered in the analysis (e.g., Slovenia, Egypt), but US and UK studies do not dominate the collected empirical evidence. For instance, while in Betthäuser et al (2023) about 71.1% of the effect sizes are derived from these studies, in our paper the corresponding figure is approximately 32.2%. 4 This makes our results of more general relevance.…”
Section: Introductioncontrasting
confidence: 42%
“…One should observe that our findings from the RVE analysis are broadly consistent with those from previous meta-analyses. Storey and Zhang (2021a) concluded that due to Covid-19 students lost, on average, 0.15 standard deviations of learning, König and Frey (2022) found average losses of 0.175 standard deviations, and Betthäuser et al (2023) estimated average losses at 0.14 standard deviations. 16 Two considerations help put these results into perspective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early in the pandemic, young people were more likely to be infected with COVID‐19 than other age groups (Wark, 2021), and some Australian research suggests that one in five appears to have had long COVID (Biddle & Korda, 2022). In addition to the direct disease impacts, lockdowns and restrictions in Australia have significantly disrupted the education (early childhood education, schooling, university or TAFE) and social lives of children and youth with implications for their mental health and education (Betthauser et al, 2023; Engzell et al, 2021; Meherali et al, 2021). 2 In some cases, the impact of the schooling disruptions was found to have negligible impacts on children's educational outcomes (Gillitzer & Prasad, 2022).…”
mentioning
confidence: 99%